GOOD TO BE BAD?. Issue 40 (9th April 2015) - Bloomfield, Paul
Abstract : It is often thought that the first question of morality is 'Why be moral?', but since it is often thought that morality opposes our happiness, it is best to start with the question, 'Why not be immoral?'. An answer is given: being immoral is self-disrespecting, and self-respect is necessary for happiness.